Cloud computing service value: A message to the board - R. Von Solms; M. Viljoen (South African Journal of Business Management, 2012)
This paper aims to alert the board to their duty of adding value to the organizations they represent by recognizing opportunities presented by new developments in information technology. Cloud computing is one such development, which is associated with opportunities and benefits. The service value that can be achieved by using this computing model will be influential in the adoption of cloud computing services. Service value is determined by the warranty and utility associated with that service. Thus, if an organization can associate itself with the utility and warranty on offer via cloud computing, it should consider the adoption of these services. Cloud computing is discussed in terms of service value. This promotes an understanding of factors to be considered when making decisions about the adoption of cloud computing.